FRI0229 Risk of Hospitalized Infections in Patients with Rheumatoid Arthritis Initiating Abatacept and Other Biologics: Analysis of A United States Claims Database. (15th July 2016) - Baker, N.; Boers, M.; Hochberg, M.; Kawabata, H.; Ray, N.; Simon, T.
Abstract : Background: Some studies have shown an increased risk of serious infection in patients with RA on biologic therapy. 1, 2 Abatacept, the first selective co-stimulation modulator for the treatment of RA, has a mechanism of action that is fundamentally different from that of other biologic agents. Objectives: The purpose of this cohort study was to compare the risk of hospitalized infection between patients initiating abatacept and patients initiating other biologic treatments. Methods: Adult patients diagnosed with RA in the MarketScan® Commercial and Supplemental Medicare database, who initiated treatment with abatacept or another biologic treatment between 1 July 2006 and 30 September 2014, were eligible for inclusion in the analysis. Patients were required to have at least 180 days of continuous health plan enrolment prior to, and ≥1 day following, initiation of the qualifying RA treatment. Patients were presumed to have initiated a treatment if there was no claim for that drug in the 180 days prior to the index date. Hence, patients initiating abatacept or another biologic may have been initiating a biologic for the first time or switching from one biologic to another. Hospitalized infections were identified by International Classification of Diseases, Ninth Revision (ICD-9) diagnosis codes indicating an infection in conjunction with a hospital stay. Patients were followed up from the date of initiation of abatacept or another biologic treatment until the event of interest, end of the initiated treatment (last treatment date plus days' supply, where the last treatment date was defined as no subsequent treatment within 90 days from last treatment date plus days' supply), end of enrolment in the database or end of data collection, whichever occurred first. Patients who were hospitalized for an infection in the 6 months prior to the date of initiation were excluded. Crude incidence rates were calculated for each cohort and a Cox regression analysis was conducted to compare patients, matched by propensity score, in the two groups. Results: A total of 18, 474 patients with RA initiating abatacept and 53, 591 initiating another biologic were identified and eligible to be included in the analysis. There were 546 incident events among abatacept initiators and 1, 716 events among other biologic initiators, resulting in crude incidence rates of 35 (95% CI: 32, 38) and 36 (34, 37) per 1000 person-years, respectively. A total of 17, 517 patients initiating abatacept and 32, 277 patients initiating another biologic were included in the matched analysis. After adjusting for prior biologic treatment, the hazard ratio comparing hospitalized infections in the abatacept cohort and the other biologic cohort was 0.97 (0.82, 1.14). Conclusions: In this study, the risk of hospitalized infection was not significantly different in patients who initiated abatacept compared with patients who initiated other biologics. References: Curtis JR, et al. Arthritis Rheum 2007;56:1125–33. Schneeweiss S, et al. Arthritis Rheum 2007;56:1754–64. Disclosure of Interest: N. Baker Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, M. Boers Consultant for: Bristol-Myers Squibb, M. Hochberg Consultant for: Bristol-Myers Squibb, H. Kawabata Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, N. Ray: None declared, T. Simon Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb